EFL Coursebooks: A Path to Reach Intercultural Communicative Competence - Fransiska Ika Prihatiningsih (Jurnal Bahasa dan Sastra, 2020)
Abstract: The globalisation of English and its rapid use among communities of speakers around the world has led the localisation of the language and the development of many varieties of English. The idea of communicative competence (CC) is being challenged through globalisation and needs to transform into intercultural communicative competence (ICC) in which EFL learners require a competence that combines both linguistic and socio-cultural skills to suit the context of the communication situation. In light of the necessity to equip EFL learners with ICC, EFL coursebooks can be used as source of exposure to the target or international cultures. This paper focuses on how EFL coursebooks can be utilized in promoting the learners’ ICC by using Byram’s framework as a bench mark. Keywords: intercultural communicative competence, EFL coursebook, intercultural communication Abstrak : Globalisasi bahasa Inggris dan penggunaannya yang cepat di antara komunitas penutur di seluruh dunia telah menyebabkan lokalisasi bahasa dan perkembangan banyak ragam bahasa Inggris. Ide kompetensi komunikatif ditantang melalui globalisasi dan perlu diubah menjadi kompetensi komunikatif antar budaya di mana pemelajar bahasa Inggris sebagai bahasa asing memerlukan kompetensi yang menggabungkan keterampilan linguistik dan sosial budaya agar sesuai dengan konteks situasi komunikasi. Mengingat kebutuhan untuk membekali pemelajar bahasa Inggris sebagai bahasa asing dengan kompetensi komunikatif antar budaya, buku pelajaran bahasa Inggris sebagai bahasa asing dapat digunakan sebagai sumber paparan budaya target atau budaya internasional. Makalah ini berfokus pada bagaimana buku pelajaran EFL dapat digunakan dalam mempromosikan kompetensi komunikatif antar budaya dengan menggunakan kerangka Byram sebagai tolak ukur. Kata-kata kunci: kompetensi komunikatif antar budaya, buku pelajaran EFL, komunikasi antar budaya